2017
DOI: 10.1002/er.3763
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anisotropic gas diffusion layers on transport phenomena in a proton exchange membrane fuel cell

Abstract: Summary The gas diffusion layer is an anisotropic porous medium, which provides pathways for the reactant gases and produced water, conducts the electrical current, removes the generated heat, and provides mechanical support. However, the gas diffusion layer is mostly considered as isotropic in numerical simulations. In the present study, a three‐dimensional, two‐phase flow, and non‐isothermal agglomerate model with consideration of anisotropic permeability, mass diffusivity, thermal conductivity, and electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…1 As a clean energy technology, PEFCs are considered as one of the most promising alternative power sources with a wide variety of applications, such as for residential community, transportation sector, and mobile, portable, and stationary applications, because of its attractive characteristics, including fast start-up ability, low temperature operation, high power density, good system efficiency, and low emissions of pollutants. [2][3][4][5][6][7] Though the fuel cell industry continues to rise, the commercialization of PEFCs is still limited, which is partly due to its stability issue. 8,9 The operating temperature greatly affects the stability and performance of the PEFC system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As a clean energy technology, PEFCs are considered as one of the most promising alternative power sources with a wide variety of applications, such as for residential community, transportation sector, and mobile, portable, and stationary applications, because of its attractive characteristics, including fast start-up ability, low temperature operation, high power density, good system efficiency, and low emissions of pollutants. [2][3][4][5][6][7] Though the fuel cell industry continues to rise, the commercialization of PEFCs is still limited, which is partly due to its stability issue. 8,9 The operating temperature greatly affects the stability and performance of the PEFC system.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer electrolyte fuel cell (PEFC) is an electrochemical device that directly converts chemical energy into electrical energy with only water and heat as the by‐products . As a clean energy technology, PEFCs are considered as one of the most promising alternative power sources with a wide variety of applications, such as for residential community, transportation sector, and mobile, portable, and stationary applications, because of its attractive characteristics, including fast start‐up ability, low temperature operation, high power density, good system efficiency, and low emissions of pollutants …”
Section: Introductionmentioning
confidence: 99%
“…The reactant transfer behaviors from flow channels to GDLs affect the reactant supplying to membrane electrode assembles, and more reactants in GDLs indicate a higher reactant supplying and higher cell performance. 16 Recent years, researchers attempted to do some researches on the design of flow field plate in the three-dimensional (3D) space. In these designs, some researches attempted to use flow channels with nonuniform flow channels, [17][18][19] and they found that the reactant transfer behaviors could be affected by the cross sections of flow channels.…”
Section: Discussionmentioning
confidence: 99%
“…What was changed was just on the two‐dimensional (2D) plane on the flow field plate, and nothing was changed in the direction which was vertical to the surface of gas diffusion layers (GDLs). The reactant transfer behaviors from flow channels to GDLs affect the reactant supplying to membrane electrode assembles, and more reactants in GDLs indicate a higher reactant supplying and higher cell performance . Recent years, researchers attempted to do some researches on the design of flow field plate in the three‐dimensional (3D) space.…”
Section: Introductionmentioning
confidence: 99%
“…Because of high cost of experiments, numerical modeling has been an effective method to investigate the water transport in PEMFC . Das et al derived an analytical model of liquid water transport across the CL of PEMFC.…”
Section: Introductionmentioning
confidence: 99%